Hubungan Disiplin Belajar dan Minat Belajar dengan Hasil Belajar PKn pada Materi Kebebasan Mengemukakan Pendapat Siswa Kelas VII di SMPS Cinta Nusa Sentul Kabupaten Bogor - Hari Indrawijaya (MODELING: Jurnal Program Studi PGMI, 2018)
This research aims to know the relationship of the discipline of study and interest in learning with the learning outcomes of this Research using a PKn. survey methods, namely: "research done on large or small populations, but the data is studied sample data drawn from the population, so that relative events found, distribution, and relations between psychological or sociological variables ". Following is the result of research: (1) the discipline of Learning (X 1) is associated with a very strong and positive Learning Outcomes PKn (Y) on the material freedom suggested in Sentul Subdistrict Nusa Tenggara Cinta SMPS Babakan Madang, Bogor regency to the value correlation of 0.947. (2) interest in Learning (X 2) connect the positive and very strong against the Learning Outcomes PKn (Y) on the material freedom suggested in Sentul Subdistrict Nusa Tenggara Cinta SMPS Babakan Madang, Bogor regency to the value of the correlation of 0.835. (3) the discipline of Learning (X 1) and interests (x 2) Learning together associated positive and very strong against the Learning Outcomes PKn (Y) on the material freedom suggested in Sentul Subdistrict Nusa Tenggara Cinta SMPS Babakan Madang, Bogor regency to the value correlation of 0.851.